Liquid-assisted grinding/compression: a facile mechanosynthetic route for the production of high-performing Co–N–C electrocatalyst materials - Kosimov, Akmal; Yusibova, Gulnara; Aruväli, Jaan; Paiste, Päärn; Käärik, Maike; Leis, Jaan; Kikas, Arvo; Kisand, Vambola; Smits, Krisjanis; Kongi, Nadezda (Royal Society of Chemistry, 2022)
Worldwide implementation of energy conversion devices such as metal–air batteries and fuel cells needs an innovative approach for the sustainable design of noble metal-free electrocatalysts. A key factor to be considered is the industry-scale production method, which should be cost and energy-effective, and environmentally friendly. A novel solid-phase-based methodology is introduced herein as a new approach for the mechanosynthesis of M–N–C-type catalysts. This method employs low-cost commercially available materials, is time and energy-efficient, results in no solvent/toxic waste and does not require a complex post-synthetic treatment. The liquid-assisted grinding/compression approach yielded a series of meso- and microporous Co–N–C catalysts, with excellent bifunctional activity towards oxygen evolution and reduction reactions. In-depth physical characterization confirmed that all NaCl-supported catalysts possess cross-linked sheet-like mesoporous carbon structures with high exposure of catalytically active sites. This study provides a new avenue for the large-scale production of high-performance and low-cost M–N–C materials via energy-effective and environmentally sustainable synthetic protocols. This journal is © The Royal Society of Chemistry.
This research was supported by the Estonian Research Council grant PSG250; and by the EU through the European Regional Development Fund (TK141, “Advanced materials and high-technology devices for energy recuperation systems” and TK143, “Molecular Cell Engineering”).
Keywords: Research Subject Categories::NATURAL SCIENCES